If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7(x + -4) = 51 Reorder the terms: 5x + -7(-4 + x) = 51 5x + (-4 * -7 + x * -7) = 51 5x + (28 + -7x) = 51 Reorder the terms: 28 + 5x + -7x = 51 Combine like terms: 5x + -7x = -2x 28 + -2x = 51 Solving 28 + -2x = 51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -2x = 51 + -28 Combine like terms: 28 + -28 = 0 0 + -2x = 51 + -28 -2x = 51 + -28 Combine like terms: 51 + -28 = 23 -2x = 23 Divide each side by '-2'. x = -11.5 Simplifying x = -11.5
| 14x=(5x+14) | | y=xk | | .3.7(-83x-3)=3.7(7x-30) | | 3x+61=6x-11 | | 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x | | 159-4x=23x+15 | | a=bc+d | | 96=5x^2-x^2 | | 41-7x=90 | | 1-5x-36x^2=0 | | 4x+1y=6 | | 3u^2-27= | | 2/1= | | 16-10w=-74 | | x-(x^2)=1 | | 5x+2x+x=8x^3 | | 5x+2x+x=8x | | 1/1= | | 64x=16x^3 | | 5x+2x+x=8 | | u^2+8u+16= | | 486=27r | | 1/-2= | | 17=1p-3-3p | | 3x-3y=15 | | a/4+3=-3 | | (x-2)(x+3)(3x+1)=0 | | 2x-80+x-50+13x+30=180 | | k/3-3=-11 | | v+8=13 |